From Challenge to Absorption: The Changing Face of Latina and Latino Studies - Pedro A. Cabán (Centro Journal, 2003)
Over the last three decades Latino studiesscholarship has gained increased academicacceptance. However, many administratorscontinue to doubt the wisdom of sustainingautonomous Latino studies departments, andare devising alternative approaches forincorporating Latino-based knowledge intothe universitys mission. This article discussesthe academys response to the emergence ofLatino studies and explores a range ofconsequences for the field of two institutionalarrangements that universities appearto privilege: the horizontal fusion with LatinAmerican Studies, and a vertical absorptioninto centers for the study of race andethnic or absorption into American studies